2022
DOI: 10.1093/stcltm/szac037
|View full text |Cite
|
Sign up to set email alerts
|

Oral Progenitor Cell Line-Derived Small Extracellular Vesicles as a Treatment for Preferential Wound Healing Outcome

Abstract: Scar formation during wound repair can be devastating for affected individuals. Our group previously documented the therapeutic potential of novel progenitor cell populations from the non-scarring buccal mucosa. These Oral Mucosa Lamina Propria-Progenitor Cells (OMLP-PCs) are multipotent, immunosuppressive, and antibacterial. Small extracellular vesicles (sEVs) may play important roles in stem cell–mediated repair in varied settings; hence, we investigated sEVs from this source for wound repair. We created an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 61 publications
1
14
0
Order By: Relevance
“…Overexpression of hTERT was not sufficient in extending CSSCs’ expansion beyond 12 passages [ 34 , 35 ]. Similar to our findings, others observed that hTERT alone was not sufficient to immortalize adipose and bone marrow derived-MSCs [ 36 , 37 ] but has been demonstrated to extend the lifespan of other cells such as oral progenitor cells [ 17 ]. The addition of other viral genes such as p53 [ 38 ], BMI-1 [ 39 ], or HPV E6/E7 [ 40 ] to hTERT overexpression has demonstrated to improve the efficacy of hTERT overexpression to produce immortalized cells.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Overexpression of hTERT was not sufficient in extending CSSCs’ expansion beyond 12 passages [ 34 , 35 ]. Similar to our findings, others observed that hTERT alone was not sufficient to immortalize adipose and bone marrow derived-MSCs [ 36 , 37 ] but has been demonstrated to extend the lifespan of other cells such as oral progenitor cells [ 17 ]. The addition of other viral genes such as p53 [ 38 ], BMI-1 [ 39 ], or HPV E6/E7 [ 40 ] to hTERT overexpression has demonstrated to improve the efficacy of hTERT overexpression to produce immortalized cells.…”
Section: Discussionsupporting
confidence: 90%
“…All newly generated cell lines, hTERT-imCSSC, c-MYC-imCSSC, and SV40T-imCSSC, extended the pCSSC lifespan. Moreover, hTERT overexpression bypasses replicative cellular senescence and prolongs cellular lifespan in vitro while retaining their progenitor/stem cells properties [ 17 , 30 , 31 , 32 , 33 ]. Overexpression of hTERT was not sufficient in extending CSSCs’ expansion beyond 12 passages [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work by our group and others demonstrated the feasibility of immortalizing MSCs from different tissues to obtain a stable parental source of MSC-SEVs [ 44 , 45 ]. In particular, the overexpression of human TERT in MSCs and other progenitors does not alter their therapeutic features or the properties of SEVs [ 46 , 47 ]. These cells can be further modified to bolster their therapeutic potential, as performed with wild-type MSCs [ 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oral mucosa lamina propria-progenitor cells (OMLP-PCs) possess unique properties, such as easy isolation, immunosuppression, and multipotency. OMLP-PC line (OMLP-PCL) exosomes were capable of decreasing myofibroblast formation and enhancing wound repopulation [ 79 ]. OMLP-PCL exosomes also achieved scar-free healing in a preclinical wound mouse model.…”
Section: Omlp-pcsmentioning
confidence: 99%